Improving Knowledge Of DMT2 Patients Through D-Edu Moving Stories (MS) At Kota Tengah Community Health Center - Suardi; Zainuddin; Sartika; Ahmad Azhar Kadim (CV. Paperhome Indonesia, 2026)
Diabetes mellitus (DM) is a chronic pancreatic disease caused by insulin deficiency or the body's inability to properly use the insulin produced. Hyperglycemia, or increased blood sugar, is one of the symptoms of DM. The purpose of Community Service is to increase the knowledge of Type 2 DM Patients Through D-EDU Moving Stories (MS) at the Kota Tengah Community Health Center. The method used is to provide counseling through D-Edu MS to DM patients at the Kota Tengah Community Health Center with a total of 35 patients. Pre and post data collection on knowledge using questionnaires. The results of the Community Service activities obtained results that there was an increase in knowledge both after the provision of D-Edu MS from 12 respondents (34.3%) to 33 respondents (94.3%). The conclusion of the activity is that providing education is very useful for patients in obtaining information in preventing and controlling DM so that serious complications do not occur.